2019
DOI: 10.1016/j.jallcom.2019.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Surface hardening by gaseous oxidizing of (Zr55Cu30Al10Ni5)98Er2 bulk-metallic glass

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The development of an IOZ is consistent with those described in Refs. [24][25]. For the present case, however, the development of an outer oxidation zone as in Refs.…”
Section: Microstructure In the Internal Oxidation Zone 22mentioning
confidence: 76%
See 3 more Smart Citations
“…The development of an IOZ is consistent with those described in Refs. [24][25]. For the present case, however, the development of an outer oxidation zone as in Refs.…”
Section: Microstructure In the Internal Oxidation Zone 22mentioning
confidence: 76%
“…%) elemental constituents in a Ti-gettered argon atmosphere. The details of the preparation procedure can be found elsewhere [24][25].…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Du and co-researchers [22] successfully reduced E. coli and S. aureus bacterial adhesion on Zr-based BMGs by femtosecond laser surface patterning, whilst having no effect on mammalian cell viability. Haratin et al [23] shown improved surface hardness of (Zr 55 Cu 30 Al 10 Ni 5 ) 98 Er 2 BMG from~600 to~1200HV using gaseous oxidising treatment, in which case a topmost Cu-rich zone formed on the surface oxide. Zhou and co-researchers [24] reported improved wear resistance of Ni-free (Zr 0.5 Ti 0.02 Cu 0.38 Al 0.1 ) 98 Y 2 BMG by thermal oxidation treatment below the glass transition temperature (T g ) of the BMG.…”
Section: Potential Solutions Limitations and Research Aimmentioning
confidence: 99%